2013
DOI: 10.1107/s0909049513021031
|View full text |Cite
|
Sign up to set email alerts
|

X-ray dynamical diffraction Fraunhofer holography

Abstract: An X-ray dynamical diffraction Fraunhofer holographic scheme is proposed. Theoretically it is shown that the reconstruction of the object image by visible light is possible. The spatial and temporal coherence requirements of the incident X-ray beam are considered. As an example, the hologram recording as well as the reconstruction by visible light of an absolutely absorbing wire are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The crystal is sufficiently thick and only the weakly absorbing mode of -polarization can be taken into account. The intensity distribution of the diffracted wave is (Balyan, 2013)…”
Section: Brief Description Of An X-ray Dynamical Diffraction Fraunhofmentioning
confidence: 99%
See 3 more Smart Citations
“…The crystal is sufficiently thick and only the weakly absorbing mode of -polarization can be taken into account. The intensity distribution of the diffracted wave is (Balyan, 2013)…”
Section: Brief Description Of An X-ray Dynamical Diffraction Fraunhofmentioning
confidence: 99%
“…The analytical analyses given by Balyan (2013) show that by multiplying (1) by exp[i( p À x) 2 /(2D)] (the coordinate axes in the diffraction plane are shown in the Fig. 1) and integrating by x over the hologram plane the numerical reconstruction of the object image can be obtained.…”
Section: Numerical Reconstruction Of An Object Imagementioning
confidence: 99%
See 2 more Smart Citations
“…Watanabe et al (2004) suggested an X-ray twozone-plates FTH scheme. X-ray dynamical diffraction holography schemes have also been presented: for example, X-ray interferometric holography (including the Momose method) (Egiazaryan & Bezirganyan, 1980;Momose, 1995;Egiazaryan, 1998;Egiazaryan et al, 1998;Balyan, 2016a,b), X-ray Fraunhofer dynamical diffraction holography (Balyan, 2013) and X-ray Fourier transform dynamical diffraction holography (Balyan, 2015). Using hard X-ray holographic methods, the reconstruction can be performed by visible light or numerical (mathematical) methods.…”
Section: Introductionmentioning
confidence: 99%